New distribution records of Gomphrena fuscipellita T. Ortuño & T. Borsch (Amaranthaceae): a rare endemic from Bolivia - Teresa Ortuño; Elmer Cuba; Daniel B. Montesinos-Tubée; Salvador Loza; Pablo Duchen (Check List)
We report on Gomphrena fuscipellita T. Ortuño & T. Borsch, a species endemic to Bolivia’s dry valleys. This species was initially described from a type specimen collected in 2005 in Cochabamba (Mizque Province) and an additional sample from Potosí (Charcas Province). However, after two decades, the species has been documented further across southern Bolivia. This study provides an updated geographical distribution, micro‑morphological trichome descriptions, and ecological insights that refine habitat characterization and advance the understanding of its ecological and geographical features.